Analysis of cable-stayed bridges under seismic loading - Tuladhar, Raju; Brotton, Derick M.; Karasudhi, Pisidhi; Wireland, Martin; DANIDA, Government of Denmark (Bangkok : Asian Institute of Technology, 1985)
New subroutines have been developed to combine with some of the existing subroutines in the program CABDAP for the purpose of seismic analysis of cable supported bridges. The developed program which is based on the step-by-step integration of the equations of dynamic equilibrium has been applied to the analysis of a cable-stayed bridge subjected to vertical and/or longitudinal ground motions. The effect of damping and the response of the bridge at the construction stage have also been studied and an investigation has been made of the properties of the integration scheme used. The program is also suitable of the analysis of cable supported bridges subjected to non-uniform ground motion and torsional motion at the supports. From the results it was concluded that the bridge is more vulnerable to the effects of vertical ground motion than of longitudinal ground motion. It was found that the response obtained for the complete bridge was larger than for the incomplete bridge, also the damping effects were found to be small when the complete bridge was analysed for the vertical ground motion. An interesting relationship was found between the critical time step and the minimum period present on the discretized structure.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Earthquakes and building; Bridges, Cable-stayed